PERMISIF DALAM SISTEM PENGENDALIAN MANAJEMEN (STUDI KASUS DALAM UD SINAR MOTOR) - Carissa Juanita Saputra; Bonnie Soeherman (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2019)
This study aims to determine the impact of permissiveness in the management control system. Management control system cannot be implemented because of permissiveness that gives looseness in management control system. Problems occur are in the form of attendance and attendance of employees, punishment is less applied with firm, tolerance in recruit employees. Writing this thesis is included in applied research where the author hopes with the writing of thisthesis can assist in providing recommendations and suggestions related to management control system in Sinar Motor. The research method used is by interview, observation and data analysis. At this writing will be discussed about the management system of the company's management Sinar Motor include action control, result control, personnel control and cultural control. However, the management control system has not been able to perform well due to permissive generated from the nature of the owner who did not bear, pity and trust. To minimize the problem, the authors provide recommendations in the form of a limitation of tolerance that can be done by the owner for each problem. With some recommendations are expected to improve management control systemUD Sinar Motor.